Therapeutic Use of Stem Cells for Myocardial Infarction - Mariah Madigan; Rony Atoui (Bioengineering, 2018)
Myocardial infarction is a leading cause of morbidity and mortality worldwide. Although medical and surgical treatments can significantly improve patient outcomes, no treatment currently available is able to generate new contractile tissue or reverse ischemic myocardium. Driven by the recent/novel understanding that regenerative processes do exist in the myocardium—tissue previously thought not to possess regenerative properties—the use of stem cells has emerged as a promising therapeutic approach with high expectations. The literature describes the use of cells from various sources, categorizing them as either embryonic, induced pluripotent, or adult/tissue stem cells (mesenchymal, hematopoietic, skeletal myoblasts, cardiac stem cells). Many publications show the successful use of these cells to regenerate damaged myocardium in both animal and human models; however, more studies are needed to directly compare cells of various origins in efforts to draw conclusions on the ideal source. Although numerous challenges exist in this developing area of research and clinical practice, prospects are encouraging. The following aims to provide a concise review outlining the different types of stem cells used in patients after myocardial infarction.